Kyoto Protocol and Greenhouse Gases Problem in Russia - A. V. Kukushkina (Московский журнал международного права)
Climate change has been recognized as a major challenge for the humankind to cope with in the 21st century. An increasing threat of unbalancing global climate system poses questions regarding elaboration of urgent measures for handling the new global situation and securing humankind and the environment from the adverse consequences of these developments. In the circumstances, a mechanism for the implementation of the Kyoto Protocol and the UN Framework convention on climate change is being created.